Financial development and economic growth – the role of mobile money: empirical evidence from Sub-Saharan Africa and a comparative study of Kenya and Uganda - Tinyinondi, Grace Ainomugisha (School of Economics, 2026)
The relationship between financial development and economic growth is well established in the finance-growth literature, which is predicated on the existence of a well-functioning financial system that underscores the complementarity between financial institutions and financial markets. Financial inclusion, defined as the participation of individuals in the formal financial system, is a critical component of financial development and, by extension, the finance-growth nexus. In many developing countries, financial exclusion remains a significant challenge, with a substantial proportion of the population lacking access to formal financial services. However, the advent of mobile money, which achieved notable success in Kenya following its introduction in 2007, has provided a considerable boost to financial inclusion across the Sub-Saharan African (SSA) region, home to the largest concentration of low-income countries globally. Empirical evidence indicates that mobile money has enhanced financial inclusion by expanding access to financial services, thereby contributing to financial development through improved resource mobilization, increased savings, and broader participation in the financial sector. Notably, SSA continues to lead globally in mobile money adoption and usage. This thesis examines the role of mobile money, an important driver of financial inclusion, in shaping the finance-growth nexus in Sub-Saharan Africa (SSA). It employs a broad measure of financial development that incorporates mobile money, financial institutions, and financial markets. The study contributes to the literature by providing empirical evidence from 17 SSA countries, selected based on data availability, covering the period from 2015 to 2022, a timeframe during which mobile money was widely adopted across the region. To gain deeper insights into the impact of enhanced financial inclusion on the finance-growth relationship in developing economies, Kenya and Uganda, two of the leading adopters of mobile money, are analyzed as case studies. While financial inclusion has gained increasing recognition, existing research on the finance-growth nexus in Kenya and Uganda often relies on a single proxy of financial development, typically bank credit to the private sector, thereby overlooking the broader dynamics of a more inclusive financial system. The study constructs a broad-based financial development index encompassing mobile money services, financial institutions, and financial markets, measured across the dimensions of depth, access, and efficiency, to offer new evidence on the finance-growth nexus in Sub-Saharan Africa (SSA), with a particular focus on Kenya and Uganda. As a robustness check, the study employs Svirydzenka's (2016) multidimensional financial development index, which has been widely adopted in recent empirical literature. The Kenyan case study utilizes annual data spanning the period 1980 to 2022, while the Ugandan analysis covers the years 1982 to 2022. To investigate the relationship between financial development and economic growth, the study applies Granger causality tests and a formal growth model. The direction of causality is examined through Granger causality tests based on a Vector Autoregressive (VAR) framework. Furthermore, the analysis incorporates the system Generalized Method of Moments (GMM) panel estimator, along with the Johansen and Juselius (1990) cointegration approach and the Vector Error Correction Model (VECM), to address potential endogeneity concerns inherent in the finance-growth relationship. The Granger causality test results for Sub-Saharan Africa (SSA) and Uganda reveal aunidirectional causality running from real GDP per capita to financial development. This finding lends empirical support to Patrick's (1966) supply-leading hypothesis, which posits that economic growth can be stimulated by the deliberate development of financial institutions and markets. In contrast, the results for Kenya are consistent with the demand-following hypothesis, also proposed by Patrick (1966), which argues that financial development occurs as a response to increasing demand generated by economic growth. These divergent patterns suggest that policy prescriptions should be context-specific: in the case of Uganda, strategies aimed at enhancing financial development may serve as a catalyst for economic growth, whereas in Kenya, promoting economic expansion may be a more effective means of fostering financial sector development. The findings based on the growth model, utilizing an overall Mobile Money Index, constructed from six mobile money indicators (i.e., the value of mobile money transactions as a percentage of GDP; number of mobile money transactions per 1,000 adults; number of registered mobile money agent outlets per 100,000 adults; number of agent outlets per 1,000 km²; mobile cellular subscriptions per 100 people; and number of registered mobile money accounts per 1,000 adults), indicate that financial inclusion positively influences the finance-growth nexus in Kenya and Uganda. However, when the analysis is disaggregated by individual mobile money indicators, the results for Sub-Saharan Africa (SSA), Kenya, and Uganda also reveal negative effects of mobile money on economic growth. This apparent contradiction suggests that, despite notable improvements, financial inclusion remains relatively low in these regions. These results are consistent with prior studies which have shown that financial development may exert a negative effect on economic growth at early stages of financial inclusion. Moreover, the findings highlight several challenges and potential risks associated with mobile money, as identified in existing literature. These include issues related to integrity, privacy, and security; limitations in infrastructure and resources; insufficient alignment of stakeholder incentives; low levels of financial literacy; and the entry of unsophisticated borrowers into the financial system. Thus, this study underscores an important policy implication: while mobile money is a critical tool for advancing financial inclusion, it does not inherently lead to positive economic outcomes. Its benefits can only be fully realized when accompanied by appropriate institutional frameworks, regulatory safeguards, and targeted policy interventions that address its associated risks.